Cetuximab in the treatment of squamous cell carcinoma of the head and neck. Issue 4 (April 2011) - Specenier, Pol; Vermorken, Jan B
The majority of the head and neck cancers are squamous cell carcinomas, which commonly overexpress the EGF receptor (EGFR). Cetuximab is a chimeric monoclonal antibody that binds with high affinity to the extracellular domain of EGFR, and in addition induces antibody-dependent cellular cytoxicity. In a randomized Phase III trial in patients with locoregionally advanced squamous cell carcinoma of the head and neck, the addition of cetuximab to radiotherapy prolonged the median time of locoregional control from 14.9 to 24.4 months and increased the median overall survival from 29.3 to 49.0 months. In patients with platinum-refractory recurrent and/or metastatic disease, the objective response and disease-control rates in various studies ranged from 10 to 13% and from 46 to 56%, respectively. In the EXTREME trial, the addition of cetuximab to platinum/5-fluorouracil as first-line treatment of recurrent/metastatic squamous cell carcinoma of the head and neck not only led to significant improvements in survival, response rate and disease control, but also induced a better symptom control in comparison with that observed with platinum/5-fluorouracil alone.